Neuroblastoma-associated opsoclonus-myoclonus-ataxia syndrome: an important yet overlooked diagnosis in pediatric ataxia - Arduç Akçay, Ayfer; Oflaz Sözmen, Banu; Erbey, Mehmet Fatih; Uysal, Serap; Kebudi, Rejin (The Turkish Journal of Pediatrics, 2026)
Background. Opsoclonus-myoclonus-ataxia syndrome (OMAS) is a rare, immune-mediated neurological disorder, often associated with neuroblastoma (NB) in children. This study aimed to describe the clinical features, diagnostic challenges, treatment, and outcomes of pediatric patients with NB-associated OMAS. Methods. We retrospectively reviewed medical records of seven children diagnosed with NB-associated OMAS between November 1, 2015 and January 31, 2025. Data on demographics, clinical presentation, tumor characteristics, treatment protocols, relapses, and outcomes were collected. The Mitchell-Pike OMS Rating Scale was used to assess severity. Results. The cohort included four girls and three boys, aged 18–36 months (median 31). All had a history of infection and/or vaccination preceding symptom onset. Ataxia was the most common initial symptom (6/7, 85.7%), followed by behavioral disturbances and sleep disorders (5/7, 71.4% each). At presentation, opsoclonus was present in two patients, which was initially misdiagnosed as nystagmus. All but one patient had opsoclonus during the disease course. Neuroblastomas were located in abdominal (n=4), thoracic (n=1), and sacral (n=2) regions; all tumors measured